Bank specific determinants of EU banks profitability after 2007 financial crisis - Ercegovac, Roberto (Array, 2020)
The basic purpose of the paper is to research determinants on profitability indicators of the banks in the European Union. Analysed bank profitability indicators considered as a standard are: the return on total bank assets (ROA) and return on total bank equity (ROE). The research model of bank profitability determinants is developed by analysing the systemically important, quoted banks in the European Union, in the 2007–2019 period, by using an adequate panel data analysis technique. The empirical evidence is in line with the initial assumptions: the efficiency of the banking firm, measured by the cost to income ratio and the non-performing loans ratio, has a significant influence on bank profitability, both on ROA and ROE. In the post-crisis period, banking firms ask for efficient cost management in achieving performance objectives. Additional important empirical results of research are the absence of impact of assets size and regulatory capital ratio on profitability indicators. The most important contribution of the paper is related to the sample definition, variable selection and explanatory power of the presented model in explaining global banking tendencies.